2012
DOI: 10.2169/internalmedicine.51.7927
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Hemodynamic Effects of Aerosolized Iloprost and Inhaled Nitric Oxide in Adult Congenital Heart Disease with Severe Pulmonary Arterial Hypertension

Abstract: Objective To compare the acute hemodynamic effects of aerosolized iloprost and inhaled nitric oxide (NO) in adult congenital heart disease (CHD) patients with severe pulmonary arterial hypertension (PAH). Methods One hundred and eighty five adult CHDs with severe PAH were nonrandomized into two groups (iloprost, n=127; NO, n=58). Various hemodynamic parameters were measured before and after iloprost or NO inhalation. Results Iloprost and NO inhalation resulted in significant reductions in pulmonary arterial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
(13 reference statements)
2
9
0
Order By: Relevance
“…In clinical studies, treprostinil showed improvements in exercise capacity, functional class, haemodynamics and survival. Moreover, iloprost inhalation resulted in significant reductions in pulmonary arterial pressure from 110.6 ± 21.8 to 105.5 ± 22.3 mmHg, and increases in pulmonary blood flow from 6.7 ± 3.3 to 9.4 ± 5.8 L·min –1 (Caojin et al ., ). Correlated with our finding, the reduction of the vasodilators in the lungs may be relevant to increased 15‐PGDH expression in pulmonary vascular intima.…”
Section: Discussionmentioning
confidence: 97%
“…In clinical studies, treprostinil showed improvements in exercise capacity, functional class, haemodynamics and survival. Moreover, iloprost inhalation resulted in significant reductions in pulmonary arterial pressure from 110.6 ± 21.8 to 105.5 ± 22.3 mmHg, and increases in pulmonary blood flow from 6.7 ± 3.3 to 9.4 ± 5.8 L·min –1 (Caojin et al ., ). Correlated with our finding, the reduction of the vasodilators in the lungs may be relevant to increased 15‐PGDH expression in pulmonary vascular intima.…”
Section: Discussionmentioning
confidence: 97%
“… 56 Some evidence is available supporting tadalafil use in combination with iloprost. 40 Finally, as demonstrated by one randomized study, tadalafil may provide additional benefit when used in combination with ambrisentan in increasing 6MWD and decreasing incidence of clinical worsening. 41 As opposed to bosentan, ambrisentan does not induce CYP3A and would not be expected to decrease tadalafil serum concentrations nor therapeutic efficacy.…”
Section: Clinical Efficacymentioning
confidence: 95%
“…In 2014, results were published from two prospective studies from the People’s Republic of China examining the efficacy of tadalafil when used in various combinations with other PAH treatments. 40 , 41 The first study was a prospective, uncontrolled, open-label evaluation of 47 patients with PAH secondary to congenital heart disease. 40 Patients received a low dose of iloprost administered as 2.5 µg inhaled six times a day for 6 months and then were started on tadalafil 5 mg once daily in combination with iloprost for an additional 6 months.…”
Section: Clinical Efficacymentioning
confidence: 99%
See 2 more Smart Citations